ENHANCEMENT OF PROJECT MANAGEMENT THROUGH ADVANCED PROJECT MANAGEMENT SOFTWARE - Manuel, Jaison (2010)
Engineering Procurement and Construction firms utilize project management information systems mainly to schedule the project activities, monitor progress of the activities, analyzing the earned value and controlling the budget. This enables project professionals to access greater information quality to enhance productivity and thereby reducing the project complexity. The selection of appropriate project management system for construction firm, implementation and use of these tools are tasks not to be taken lightly. This paper describes selection, utilization, adoption and factors that impact the effective application of project management information systems. Author’s experience with Engineering Procurement and Construction firm has motivated to highlight the issues affecting project management software system in the case study and survey has collected the issues in usage of project management software system. The practical issues affecting the accuracy of base line schedules in project management software system were analyzed. The dependency of planning experts upon work in progress updates that helps to verify the base line schedule is analyzed through the potential of contemporary techniques to collect just in time field updates. The variations in attitude of management that impact the effective application of project management software system were analyzed. The selection criteria for an advanced project management information system covering the entire life cycle of project initiation, planning, execution and termination were described to manage entire project portfolio and project programs. Finally, the paper addresses the crucial success and failure factors of project management information systems that management needs to understand for successful implementation. Understanding the factors in selection, utilization and implementation of project management information system enables better management of Engineering Procurement and Construction projects with project management information systems.